Network heterogeneity regulates steering in actin-based motility - Rajaa Boujemaa-Paterski (Nature Portfolio, 2017)
Protrusive cellular structures contain a heterogeneous density of actin, but whether this influences motility is not known. Using an in vitro system and modelling, here the authors show that local actin monomer depletion and network architecture can tune the rate of network growth to impose steering during motility.